People at the Heart of Corporate Governance: Reimagining the Role of HRM. Issue 4 (October 2019) - Sripada, Chandrasekhar
Abstract: People, talent and culture aspects are not yet the mainstream agenda for corporate governance. Corporate governance literature has been largely concerned with shareholder interests. Even where the broader discourse has moved to 'stakeholder' interests, the talent agenda has been rather muted. In this article, we examine the current literature on corporate governance and identify the gaps related to talent and culture topics. We argue that since people are not yet at the heart of corporate governance, human resource management (HRM) is not a priority for boards. However, we explain why the 4Cs of HRM, namely Compliance, Compensation, Competence and Culture—in their broader sense—should be central concerns of corporate governance. Apart from building a case for redirecting the agenda of corporate governance with people at its centre, this article provides some general guidance on how this can be operationalised in the near term. There is clearly a need for further research on how corporate governance can be enriched by including the people agenda. Simultaneously, we need to reimagine the HRM function as a vital arm in shaping and steering the future of corporate governance.